Association between metabolic profiles in urine and bone mineral density of pre- and postmenopausal Chinese women. Issue 1 (January 2019) - Yu, Lisha; Qi, Huanhuan; An, Guohua; Bao, Jun; Ma, Bo; Zhu, Jianwei; Ouyang, Gang; Zhang, Pengling; Fan, Hongwei; Zhang, Qi
Abstract: Objective: In the present study, we aimed to characterize the pathological development of menopausal osteoporosis, as well as to explore potential biomarkers and metabolic pathways involved in osteoporosis. Methods: Urine samples from 322 female participants categorized by menopause status and different bone conditions were collected and analyzed based on a gas chromatography–mass spectrometry (GC–MS) approach. Multivariate and univariate statistical analyses were carried out for urinary metabolomic profile characterization and comparison. Results: Seventeen metabolites in the low bone mineral density (BMD) groups were clearly differentiated from those in normal BMD groups. Among these 17 differentiating metabolites, taurine, β-alanine, and 5-hydroxycaproic acid were found to be potential biomarkers of osteoporosis. The taurine metabolic pathway and the β-alanine metabolic pathway were found to be related to menopause and bone loss. Conclusions: Based on the GC–MS metabolomic platform, four typical pathological phases during the progression of postmenopausal osteoporosis were described. Several differentiating metabolites and metabolic pathways were found to be closely related to the pathology of postmenopausal osteoporosis. Our results provided a solid foundation for further studies on early diagnosis and pathomechanistic evaluation. Abstract : Supplemental Digital Content is available in the text